2005
DOI: 10.1118/1.1855031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of and compensation for spatial noise of LCDs in medical applications

Abstract: Recent developments in liquid crystal display (LCD) technology suggest that this technology will replace the cathode ray tube (CRT) as the most popular softcopy display technology in the medical arena. However, LCDs are far from ideal for medical imaging. One of the principal problems they possess is spatial noise contamination, which requires accurate characterization and appropriate compensation before LCD images can be effectively utilized for reliable diagnosis. This paper presents some work we have conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…The remarkable higher resolution [1,2] than that is provided by the cathode ray tube (CRT) display is the most important feature of the LCDs. However, their noise properties seemed not to be good, as described in recent papers [2][3][4]. Moreover, the method of evaluation of the noise property is not welldefined because of problems in the treatment of signal components generated from discrete and complicated pixel structures.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The remarkable higher resolution [1,2] than that is provided by the cathode ray tube (CRT) display is the most important feature of the LCDs. However, their noise properties seemed not to be good, as described in recent papers [2][3][4]. Moreover, the method of evaluation of the noise property is not welldefined because of problems in the treatment of signal components generated from discrete and complicated pixel structures.…”
Section: Introductionmentioning
confidence: 91%
“…Recent researchers employed common measurement procedures for the NPS measurement of LCDs, in which LCD images were captured digitally by cameras with charge-coupled devices (CCD), and a two-dimensional (2D) fast Fourier transform (FFT) was used [2][3][4]. In addition, pixel-aligned numerical apertures (PAs) that average the CCD data within the area corresponding to one LCD pixel were commonly applied for evaluation of the noise property, which was separated into inter-and intrapixel variations.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,6), whereas works reported by others seem to conclude that FP performance is superior to that of CRT's. 5,7 A very detailed study of 32 different FPs described in Ref. 8 found that at optimized viewing conditions, the narrow viewing angles of the AMLCD displays need to be taken into account when changing from CRT to FPs.…”
Section: Introductionmentioning
confidence: 99%
“…The SHR-LCDs achieve a threefold higher-resolution than do current LCDs in only the sub-pixel direction [4,5,9,10]. Therefore, as the SHR-LCDs provide higher resolution only in the sub-pixel direction, it is necessary to carefully investigate their effectiveness for displaying digital mammograms.…”
Section: Introductionmentioning
confidence: 99%